The RELATIONSHIP OF CLEAN AND HEALTHY LIFE BEHAVIOR TO ILLNESS IN TODDLERS - Lailatul Fitria Sahid; Irwanto; Wahyul Anis (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2021)
Background: Childhood is susceptible to disease. One cause of illnesses in infants is due to unhealthy environmental conditions. Therefore, health efforts need to be done to prevent the emergence of diseases caused by the environment by behaving clean and healthy (PHBS). Method: observational analytic case control design. The number of samples was 142 toddlers with 71 respondents each in the case and control groups selected by consecutive sampling technique. Data were collected using questionnaires and illness reports from the health center. Data analysis used Chi Square with. Results: Chi Square test results with 5% α indicated delivery assisted by health workers (cannot be analyzed), exclusive breastfeeding (p=0.00), washing hands with soap and water (p=0.00), eradicating larvae once a week (p=0.00), not smoking at home (p=0.00), and healthy life behavior (p=0.00). Conclusion: there was a relationship of exclusive breastfeeding, washing hands with soap and water, eradicating larvae once a week, and not smoking in the house to the incidence of illness in infants